A Study on the Algicidal effects of Iraqi Indigenous plant extracts. - A.Razzak, A.A. W.; AL-Bashir, N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The Ethanolic extracts of different Iraqi indigenous plants which belong to different families showed algicidal activity against Anabaena, Nostoc and Myxosarcina species. Peganum harmala extract was the most potent in controlling the growth of tested Cyanobacterial species